Gait Characteristics in Patients With Chronic Obstructive Pulmonary Disease - Nopakoon Nantsupawat; Paige Lane; Ornwadee Siangpraipunt; Swetha Gadwala; Kenneth Nugent (SAGE Publishing, 2015)
Background: Patients with chronic obstructive pulmonary disease (COPD) have reduced gait speeds and more frequent falls. We analyzed gait characteristics and fall risk in these patients using video recordings and questionnaires to determine if these patients had any quantitative changes in gait characteristics and to determine if screening for fall risk provided useful information. Methods: Patients with COPD who had participated in pulmonary rehabilitation completed a short history falls and the Activities-Specific Balance Confidence Scale questionnaire. They performed the Get Up and Go Test. Their typical gait was video recorded and analyzed with Dartfish software. Results: Fourteen patients completed this study. The mean age was 69.7 ± 6.0 years, and the mean forced expiratory volume in 1 second was 1.01 ± 0.38 L (36.9% ± 15.6% predicted). Three patients had a history of falls without significant injury. The mean Activities-Specific Balance Confidence Scale score was 91.8 ± 14.9, but the scores ranged from 10 to 100. Patients reported decreased balance confidence when "stepping onto or off an escalator while holding onto parcels." The mean time in the Get Up and Go Test was 11.9 ± 2.0 seconds. Spatiotemporal parameters of gait included mean step length 0.65 ± 0.6 m, mean double support time 0.36 ± 0.05 seconds, mean double support time ratio 30.4% ± 3.1%, average free walking speed 65.3 ± 6.9 m/min, and number of steps per minute 100.4 ± 8.8. The speed was significantly slower and the double support time was significantly longer when compared with normal values. Conclusions: Most patients had good balance confidence scores. Their gait and balance were qualitatively normal using the Tinetti tools for assessment. Therefore, their risk for falls seems low. They had a reduced step length and increased time spent in double support, changes which might represent subtle adaptations to reduced balance.